Erythroderma and Chronic Lichenification Due to Metformin - Javier Moreno Díaz; Jose Miguel García Bruñén; Rocío Bermúdez Cameo; Ana Martínez González (European Journal of Case Reports in Internal Medicine, 2019)
We present the case of a 62-year-old man with a 4-year history of pruritus and erythroderma. The patient had been taking metformin for 5 years, so after contact allergies, contact with toxic products, and autoimmune diseases were ruled out, the condition was treated as erythroderma secondary to metformin. A skin biopsy subsequently confirmed the diagnosis and lichenification of some areas of the patient's skin.